Synthesis of Flower-Like Cu2ZnSnS4 Nanoflakes via a Microwave-Assisted Solvothermal Route - Fei Long; Shuyi Mo; Yan Zeng; Shangsen Chi; Zhengguang Zou (International Journal of Photoenergy)
Flower-like Cu2ZnSnS4 (CZTS) nanoflakes were synthesized by a facile and fast one-pot solution reaction using copper(II) acetate monohydrate, zinc acetate dihydrate, tin(IV) chloride pentahydrate, and thiourea as starting materials. The as-synthesized samples were characterized by X-ray diffraction (XRD), Raman scattering analysis, field emission scanning electron microscopy (FESEM) equipped with an energy dispersion X-ray spectrometer (EDS), transmission electron microscopy (TEM), and UV-Vis absorption spectra. The XRD patterns shown that the as-synthesized particles were kesterite CZTS and Raman scattering analysis and EDS confirmed that kesterite CZTS was the only phase of product. The results of FESEM and TEM show that the as-synthesized particles were flower-like morphology with the average size of 1~2 μm which are composed of 50 nm thick nanoflakes. UV-Vis absorption spectrum revealed CZTS nanoflakes with a direct band gap of 1.52 eV.